2020
DOI: 10.1002/advs.202000176
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Axial Hydroxyl Ligand on FeN4C Electrocatalysts and Its Impact on the pH‐Dependent Oxygen Reduction Activities and Poisoning Kinetics

Abstract: FeNC materials have shown a promising nonprecious oxygen reduction reaction (ORR) electrocatalyst yet their active site structure remains elusive. Several previous works suggest the existence of a mysterious axial ligand on the Fe center, which, however, is still unclarified. In this study, the mysterious axial ligand is identified as a hydroxyl ligand on the Fe centers and selectively promotes the ORR activities depending on different FeN4C configurations, on which the adsorption free energy of the hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 42 publications
11
93
0
Order By: Relevance
“…To further confirm the role of MnN 4 sites, the SCN − poison experiment was also carried out to block the MnN sites. [ 43 ] The introduction of SCN − into the ORR system of Mn‐SAS/CN caused an obvious negative shift of the half‐wave potential by 90 mV and notably reduced diffusion limiting current density (≈84% retention), while no obvious change was found in as‐prepared porous CN, indicating that the MnN 4 sites constitute the key catalytically active centers of ORR (Figure 2f). In addition, the stability of Mn‐SAS/CN during ORR was tested by CV (Figure 2e), and the characterizations including XRD, transmission electron microscopy (TEM), and AC HAADF‐STEM images were taken for the Mn‐SAS/CN after 5000 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm the role of MnN 4 sites, the SCN − poison experiment was also carried out to block the MnN sites. [ 43 ] The introduction of SCN − into the ORR system of Mn‐SAS/CN caused an obvious negative shift of the half‐wave potential by 90 mV and notably reduced diffusion limiting current density (≈84% retention), while no obvious change was found in as‐prepared porous CN, indicating that the MnN 4 sites constitute the key catalytically active centers of ORR (Figure 2f). In addition, the stability of Mn‐SAS/CN during ORR was tested by CV (Figure 2e), and the characterizations including XRD, transmission electron microscopy (TEM), and AC HAADF‐STEM images were taken for the Mn‐SAS/CN after 5000 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, unlike in acidic media, the ORR performance in alkaline media finally recovered to the original level of the continuous linear sweep voltammetry (LSV), which was ascribed to the dissociation of SCN − in 0.1 m KOH solution [38] . It is worth noting that recent studies have revealed that the competitive adsorption between the hydroxyl ligand and poisoning anions leads to new pH‐dependent poisoning kinetics of Fe−N−C catalysts [22] . It was observed that the ORR activity declined obviously in acidic solution, but there did not alter significantly in alkaline solution.…”
Section: Identification Of Active Sites For M−nx/c Catalystsmentioning
confidence: 96%
“…[38] It is worth noting that recent studies have revealed that the competitive adsorption between the hydroxyl ligand and poisoning anions leads to new pHdependent poisoning kinetics of FeÀ NÀ C catalysts. [22] It was observed that the ORR activity declined obviously in acidic solution, but there did not alter significantly in alkaline solution. This interesting result indicates significantly various poisoning mechanisms at high or low pH, which is mainly caused by the competitive adsorption between OH ligand and poisoning anions, especially in alkaline solution, which can be evidenced by the electrochemical experiments and theoretical calculations.…”
Section: Mà N X Moietiesmentioning
confidence: 98%
See 2 more Smart Citations